Айзек и яйцо: [роман] / Бобби Палмер - Палмер Бобби (Inspiria, 2023)
Экземпляры: ЦБ (20230511) / Инвентарный номер: 58860 / Цена: 408.79 / Сис.шифр: 84(4/8) / Авт.знак: П 14 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44